Strengthening State Control over the Implementation of Legislative Acts - Yangiboyev , Norquvvat; Rustamova , Elnora; Umirov , Bobomurod; Sanginova , Gulnoza (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the theoretical and legal foundations, as well as practical mechanisms, for strengthening state control over the implementation of legislative acts. In particular, it highlights issues related to ensuring the supremacy of law in the activities of state bodies, strengthening executive discipline, and improving accountability measures. The article also examines the essence of the control institution, its types and forms, as well as ways to increase the effectiveness of control through the use of digital technologies in modern governance systems.